Palm-Sized Single-Shot Full-Color Incoherent Digital Holographic Camera System with White Light - Tatsuki Tahara; Tomoyoshi Shimobaba (Advanced Devices & Instrumentation)
The realization of full-color motion-picture holographic imaging with daily-use light is an important research objective. To achieve it, various types of single-shot phase-shifting incoherent digital holography (SSPS IDH) systems have been proposed up to now. Portability of the holography system is now strongly required to enable the application of holographic imaging to various scenes. Here, we propose a palm-sized full-color digital holographic camera system that can achieve both single-shot full-color incoherent holographic imaging and downsizing. An SSPS IDH system with a color polarization image sensor is adopted, and a compact optical system exploiting 2 thin polarimetric phase-modulation optical elements is constructed. Full-color motion-picture holographic imaging at the frame rate of the image sensor is experimentally demonstrated using white light with a continuous-wavelength spectrum. This camera enables full-color 3D motion-picture recording under the condition that a reflective object is set close to the holographic camera. An antivibration structure is no longer needed.